Back-scattering and neutralization coefficients of nitrogen ions on iron surface - Kuzmichev, A.; Melnichenko, M. (Problems of Atomic Science and Technology, 2022)
The coefficients of back-scattering and neutralization of nitrogen ions (N⁺) on iron surface during ion bombardment at the processes of ion sputtering and niriding have been calculated using TRIM code. The pure iron target and two-element targets, Fe+Mo (1 and 5%), Fe+W (1 and 5%), were tested. The ion energy was from 0.1 to 70 keV. The ions N+ are considered to be back-scattering in the form of energetic N atoms. The calculations showed the back-scattering and neutralization coefficients are tens of percent for low energies N⁺ ions and several percent for energies of tens kiloelectron-volts. The average penetration depth of the ions into the Fe target and the ion sputtering coefficients are calculated, too.